Methionine Restricted Diet; Clinical Application - Günebak Şahin, Tuba; Şahin, Nihal; Besler, Tanju; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2012)
To review nutritional therapy of hyperhomocysteinemia observed in Methylenetetrahydrofolate Reductase (MTHFR) gene polymorphisms. The researches and review articles about the subject has been read, investigated, compiled and integrated with our clinical experience. In the therapy of MTHFR gene polymorphisms, nutritional therapy is an integral part of the therapy and methionine restricted diet should be encouraged with vitamin supplementation which have important functions in methionine-homocysteine pathways. Methionine restricted diet may hneave beneficial effects on serum/plasma total homocysteine levels of the patients with MTHFR enzyme polymorphisms.